Effect of storage conditions and antioxidant additives on the deterioration of biodiesel and biodiesel blends - Kah, Beverly Waynee (2014)
Biodiesel is often used as a substitute of diesel fuel in current market. However, the inherent structure remains a significant problem due to its oxidation stability. Most industries blend biodiesel in certain percentages of diesel to prolong the shelf life, which lead to the aims of this study, to clarify and to investigate the storage stability of biodiesel and biodiesel blends under various type of storage effect over storage time of 8 months with few different conditions. Results show that storage with exposure of ambient air deteriorate faster compare to sample without exposure. Deteriorated percentages were faster for B100 > B30 > B20 > B0. Biodiesel with different blending percentages with Ultra Low Sulphur Diesel (ULSD) were also investigated. Additives added during desulfurization process for ULSD gives different trend compare to normal diesel. Water content, peroxide value and total acid number increased with respect to time. Upon exposure to air and under high temperature (heat) condition during storage, biodiesel and biodiesel blend is more susceptible to deteriorate due to its chemical structure. 2 layers of fuel as upper layer and sludge as bottom layer were formed after deterioration. Fuel analysis showed a drastic increase in the acid value, viscosity, oxidation product compound when the fuel deteriorated after 24 hours. Deterioration compound were examined, which demonstrated that aldehyde, ketones, short chain carboxylic acids as dominant compounds. As oxidation cannot be completely prevented, biodiesel and biodiesel blends user can only slow down the deterioration by adding sufficient antioxidant. Therefore the efficacy of selected antioxidant additives, Ecotive, Petrolift, Butylated Hydroxytoluene (BHT), Tert-Butylhydroquinone (TBH), and 2,2'-methylene-bis(4-methyl-6-tert-butylphenol) (MBP), in soy methyl esters (SME), palm methyl esters (PME) and jatropha methyl esters (JME) was investigated. These five antioxidant additives were selected for further studies at dosage percentages from 0.1 wt%, 0.5 wt% and 1.0 wt% and effect on different blending percentages. The antioxidant additives were measured in EN14112 Oxidation Stability under EN standard method, and protection factor (PF). Results showed that phenolic additives TBH give a better PF to comparing to other additives. It possesses two hydroxyl groups (OH-) attached to the aromatic ring, thus on the basis of its electronegativity offer more sites for the formation of the complex between the free radical and antioxidant radical for the stabilization of the ester chain. The present finding is able to provide general guideline on additives selection and information on their performance. Results shows that efficacy of antioxidant rank from Petrolift < BHT < Ecotive < TBH & MBP. Effectiveness and performance of antioxidants did not influence by biofuel feedstock. Oxidation of biodiesel is fully depending on unsaturated fatty acid and position of allylic and bis-allylic on fatty acid. Results also showed that additives able to perform better with the present of higher diesel percentages in biodiesel blends. The higher the diesel percentages in diesel the better the additive can improve its IP.These results are sufficient enough to provide a biodiesel and biodiesel blends storage and prevention guideline according to storage conditions, fuel types and blending percentages to end user and to support the products of Yanmar.